PENERAPAN METODE CPM DAN GRANTT CHART UNTUK MENGUKUR EFISIENSI WAKTU (Studi Kasus Pembangunan Rumah Perum GIP Kertosono, Nganjuk) - Rony Kurniawan (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
The implementation of housing unit construction needs to be done in order to control time efficiently. Therefore, the delay of the house will result in inefficient costs. This study aims (1) to determine the scheduling sequence of the type 45/90 residential development project at Perum GIP Kertosono, Nganjuk (2) to determine the network or network in the type 45/90 residential development project at Perum GIP Kertosono, Nganjuk (3) To understand] the critical activities carried out in the housing construction project type 45/90 at Perum GIP Kertosono, Nganjuk, (4) To find out the activities carried out jointly in the housing construction project type 45/90 Perum GIP Kertosono, Nganjuk. This research uses the Critical Path Method (CPM) or the critical path and the Grantt Chart method. The application of the CPM method is used to determine the time for effective and efficient development projects. While the grantt chart method is used to determine the activities carried out and the busiest time in the housing development project activities. Through the application of CPM resulted in efficient development implementation with a time of 84 days or 19 days faster than the total time predicted by the planning team for 103 working days. Through the grant chart method, it was found that the busiest times of construction were on the 16th to the 53rd day because at that time it was carried out simultaneously with the installation of sloofs, concrete columns, installation of floor tiles and construction of terraces.